Arah dan Tujuan Pemidanaan dalam Hukum Pidana Nasional Indonesia - Ahmad Bahiej (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2012)
Punishment is one of the core issues in a significant criminal law. Discussionabout punishment and purpose / justification of punishment has become a lengthydiscussion even stranger since the criminal law itself. Even the way the Indonesiancriminal law, sentencing the topic of discussion of the drafter of national criminal law.Of course, all agreed that the determination of the type of punishment in a national lawbuilding will depend on a philosophical view: how the goals of punishment that will bebuilt within the legal system. In observance of the law of Indonesia travel records sincepre-colonial times to the national law of development efforts can be concluded that thepurpose of sentencing under Indonesian criminal law will be brought to the convictionthat moderate and better.